Non-classic features of pseudohypoparathyroidism type 1A - Shoemaker, Ashley H. (Curr Opin Endocrinol Diabetes Obes, 2017)
PURPOSE OF REVIEW: To provide readers with a review of contemporary literature describing the evolving understanding of the pseudohypoparathyroidism type 1A (PHP1A) phenotype. RECENT FINDINGS: The classic features of PHP1A include multi-hormone resistance and the Albright Hereditary Osteodystrophy phenotype (round facies, short stature, subcutaneous ossifications, brachydactyly, and early-onset obesity. Obesity may be due to a decrease in resting energy expenditure since most patients do not report significant hyperphagia. Patients with PHP1A have an increased risk of type 2 diabetes. In addition to brachydactyly and short stature, orthopedic complications can include spinal stenosis and carpal tunnel syndrome. Hearing loss, both sensorineural and conductive, has been reported in PHP1A. Additionally, ear-nose-throat findings include decreased olfaction and frequent otitis media requiring tympanostomy tubes. Sleep apnea was shown to be 4.4-fold more common in children with PHP1A compared with other obese children; furthermore, asthma-like symptoms have been reported. These new findings are likely multifactorial and further research is needed to better understand these non-classic features of PHP1A. SUMMARY: Along with the Albright Hereditary Osteodystrophy phenotype and hormone resistance, patients with PHP1A may have additional skeletal, metabolic, ear-nose-throat and pulmonary complications. Understanding these non-classic features will help improve clinical care of PHP1A patients.